1996
DOI: 10.1071/rj9960033
|View full text |Cite
|
Sign up to set email alerts
|

Run-Off and Soil Movement on Mid-Slopes in North-East Queensland [Australia] Grazed Woodlands.

Abstract: Run-off, bedload and sediment concentration data were collected over a five-year period from unbounded catchments in grazed and exclosed pastures in woodlands. Cover varied from 4% during drought conditions to almost 100% in exclosed areas after above-average rainfall. High bedload soil loss, sediment concentration and run-off percentages were associated with low cover (<30%). Run-off as a percentage of rainfall increased linearly with rainfall intensity; decreased linearly with cover; decreased slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 0 publications
2
50
1
Order By: Relevance
“…This phenomenon has been scarcely analysed: most previous studies depict hydrological heterogeneity for stable systems throughout the world where sources and sinks are coupled under a dynamic equilibrium state (Ludwig et al, 1997(Ludwig et al, , 2005, or address the stability of coupled systems under several types of disturbances, mainly fires and overgrazing, which reduce vegetation cover, and thus runoff obstruction, increasing runoff and erosion rates (Wilcox et al, 2003;McIvor et al, 1995;Scanlan et al, 1996). Our research describes the variation of the sink-source pattern in a gradient of ecological recovery (driven by a gradient of overland flow volume) after slope reclamation.…”
Section: Slope Scale Hydrological Heterogeneity: Effects Of Overland mentioning
confidence: 99%
“…This phenomenon has been scarcely analysed: most previous studies depict hydrological heterogeneity for stable systems throughout the world where sources and sinks are coupled under a dynamic equilibrium state (Ludwig et al, 1997(Ludwig et al, , 2005, or address the stability of coupled systems under several types of disturbances, mainly fires and overgrazing, which reduce vegetation cover, and thus runoff obstruction, increasing runoff and erosion rates (Wilcox et al, 2003;McIvor et al, 1995;Scanlan et al, 1996). Our research describes the variation of the sink-source pattern in a gradient of ecological recovery (driven by a gradient of overland flow volume) after slope reclamation.…”
Section: Slope Scale Hydrological Heterogeneity: Effects Of Overland mentioning
confidence: 99%
“…The influence of ground cover on runoff and soil movement in small plots highlights the relationship between sparse (<40%) ground cover and runoff generation [19]. However, for very large events with high rainfall intensities (>100 mm/h), cover had little influence on runoff [18,19]. In all these aforementioned studies, only temporal variability of rainfall was considered, not spatial variability throughout the catchment.…”
Section: Introductionmentioning
confidence: 99%
“…At smaller scales (i.e., plot), studies have established that annual runoff varies considerably with the spatial distribution of ground cover [17]; however, cover may have little effect on overland flow during very large rainfall events (>100 mm with intensities between 45 and 60 mm/h) when the landscape is inundated with surface runoff due to Hortonian overland flow processes [18][19][20]. Roth [21] showed that high ground cover values (>75%) can promote infiltration during high intensity events.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of ground cover on runoff and soil movement in small plots highlights the relationship between sparse (<40%) ground cover and runoff generation [19]. However, for very large events with high rainfall intensities (> 100 mm/h), cover had little influence on runoff [18,19]. Several studies in the GBR have shown that converting forest to pasture can increase runoff by ~80% at sub-catchment scales [27] and ~40% for river basin scales [28].…”
Section: Introductionmentioning
confidence: 99%
“…At the smaller scale (i.e., plot), studies have established that annual runoff varies considerably with the spatial distribution of ground cover [17], however, cover may have little effect on overland flow during very large rainfall events (>100 mm with intensities between 45-60 mm/hr) when the landscape is inundated with surface runoff due to Hortonian overland flow processes [18][19][20]. Roth [21] showed that high ground cover values (>75%) can promote infiltration during high intensity events.…”
Section: Introductionmentioning
confidence: 99%